Effects of feeding direction on the hulling of paddy grain in a rubber roll huller. (July 2019) - Chen, Peiyu; Jia, Fuguo; Liu, Hanru; Han, Yanlong; Zeng, Yong; Meng, Xiangyi; Xiao, Yawen; Li, Gengrun
Abstract : The low ratio of one-time hulling is one of the main factors restricting the development of rice processing. Understanding the hulling mechanism and the effect of feeding direction of paddy grain on the hulling performance is the key to increasing the one-time hulling ratio of rubber roll hullers, but the mechanism remains poorly understood. In this work, the effects of the feeding direction on rotation movements were explored using the discrete element method (DEM), observing the microstructure of paddy grain, and conducting the static shearing experiments. The effect of feeding direction on the hulling ratio and hulling pattern were investigated. The results showed that rotation angle increases as feeding direction increases and the axis of rotation of the grain changes from the short to long axis. This difference in rotation leads to differences in the shearing effect of the rubber rolls on the apexes of the grain. From the microstructure of the grain it can be seen that the grain core is wrapped by the lemma and palea under a process of bonding and interlocking. The experimental results show that the process of hulling destroys bonding and interlocking by a shearing action. Therefore, hulling ratio changes with changes in feeding direction. The results were confirmed by hulling experiments using a rubber roll huller and it was verified that feeding direction has a significant effect on the breakage ratio. Highlights: The mechanism of hulling is to release the bond and the interlocking between lemma. Different feeding direction affects stresses and rotation of paddy in hulling process. Hulling performance is related to the feeding direction of paddy grain. The vertical feeding of paddy can effectively increase hulling performance.